Another Law in Indonesia: Customary Land Tenure System Coexisting with State Order in Mutis Forest - Imam Budiman; Takahiro Fujiwara; Noriko Sato; Dani Pamungkas (Institut Pertanian Bogor (IPB University), 2020)
Local wisdom has been coexisting with the state system in several places in Indonesia. The Mountain Mutis Nature Reserve in East Nusa Tenggara province is the strict nature reserves, but a customary land tenure system, called suf, exists so far in the nature reserve. The objectives of this study are (1) to organize the historical territorialization process, (2) to clarify the customary land tenure system and activities for livelihoods by local people, and (3) to discuss the challenges of its land tenure system to manage forests sustainably as well as policy methods to harmonize legal pluralism in Mutis Area. Field observation and in-depth interviews with key informants were employed for data collection, and the collected data were analyzed by a qualitative descriptive method. The findings showed the traditional reward and punishment systems regarding extracting non-timber forest products, grazing livestock, and preventing forest fires were working well for sustainable forest management. However, increased pressure on forests due to future population growth appears to have an impact on the traditional system. It also showed the government officers and local people started some discussions to recognize the suf in the formal legal order. However, there were institutional problems to introduce current state systems. Therefore, it is required to flexibly operate or revise the state laws according to the actual situation to harmonize society between state and people.